A novel HLA‐A*24 allele, HLA‐A*24:512, identified by next‐generation sequencing in a Chinese individual. (3rd December 2020) - Wang, Linlin; Wang, Yan
Abstract : The new allele HLA‐A*24:512 showed one nucleotide difference compared to A*24:02:01:01 at position 548 (A > G).